Evolution toward transdisciplinarity in technology and resource management research: The case of a project in Ethiopia - Jabbar, M.A.; Mohamed-Saleem, M.A.; Li Pun, H.H. (Birkhauser Verlag, 2001)
Development is a human problem aimed at changing humans and their economic, social, and ecological environments. Throughout history, humans have acquired new knowledge to shape their future. As their needs multiplied and became more complex, science and technology processes of systematic inquiry for acquiring and applying knowledge have exerted increasing influence on human life, society, and the environment. To address the complexity and multiplicity of problems, scientific research has been divided into disciplines by problem areas. It has also been divided into basic, strategic, and applied or adaptive orientations, depending on whether the objective is to search for new horizons in knowledge or to adapt a known technology in a different situation. These changes have resulted in divisions of labor in knowledge production and application, and they have contributed to a phenomenal increase in output, income, and human welfare. This chapter focuses on a particular project, examining the limitations of disciplinary research to solve complex problems and the potential role of transdisciplinary research to overcome them. The main topics of discussion include need for transdisciplinary research; problems of highland Ethiopia and some related research; and from vertisols and watershed management to integrated resource management.